Parkinson’s disease deficits in time perception to auditory as well as visual stimuli – A large online study - Su, Zi H.; Patel, Salil; Bredemeyer, Oliver; FitzGerald, James J.; Antoniades, Chrystalina A. (Frontiers in Neuroscience, 2022)
Cognitive deficits are common in Parkinson’s disease and range from mild cognitive impairment to dementia, often dramatically reducing quality of life. Physiological models have shown that attention andmemory are predicated on the brain’s ability to process time. Perception has been shown to be increased or decreased by activation or deactivation of dopaminergic neurons respectively. Here we investigate differences in time perception between patients with Parkinson’s disease and healthy controls. We have measured differences in sub-second and second time intervals. Sensitivity and error in perception as well as the response times are calculated. Additionally, we investigated intra-individual response variability and the effect of participant devices on both reaction time and sensitivity. Patients with Parkinson’s disease have impaired sensitivity in discriminating between durations of both visual and auditory stimuli compared to healthy controls. Though initially designed as an in-person study, because of the pandemic the experiment was adapted into an online study. This adaptation provided a unique opportunity to enrol a larger number of international participants and use this study to evaluate the feasibility of future virtual studies focused on cognitive impairment. To our knowledge this is the only time perception study, focusing on PD, which measures the differences in perception using both auditory and visual stimuli. The cohort involved is the largest to date, comprising over 800 participants.